2021
DOI: 10.1186/s13567-021-00896-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chicken macrophage functions and gene expressions following infectious bronchitis virus M41 infection

Abstract: Infectious bronchitis virus (IBV) is a pathogenic coronavirus with high morbidity and mortality in chicken breeding. Macrophages with normal biofunctions are essential for host immune responses. In this study, the HD11 chicken macrophage cell line and chicken peripheral blood mononuclear cell-derived macrophages (PBMCs-Mφ) were infected with IBV at multiplicity of infection (MOI) of 10. The dynamic changes of their biofunctions, including cell viability, pathogen elimination function, phagocytic ability, and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…Autophagy can be both activated and inhibited in renal carcinoma, and it plays a double-edged role in the development of renal carcinoma [ 8 , 9 ]; in the early stage of cancer, autophagy can suppress tumors, while in the late stage, autophagy contributes to the survival of tumor cells in an unfavorable environment, and some autophagy-related proteins P62, LC3B, and beclin-1 have become indicators of the prognosis of patients with renal carcinoma [ 10 , 11 ]. Autophagy is a dynamically changing process [ 12 , 13 ], and this experiment was conducted to map the autophagy time point, and the results showed that the activation of autophagy was more obvious when ursolic acid acted on 786-O cells at 24 h. Therefore, the time point of the subsequent experiment was set to 24 h. It was found that ursolic acid could increase the expression level of LC3II protein in 786-O cells, which is considered as autophagy. However, the reason for this may be the increased autophagosome production and also the blocked degradation phase of autophagosomes, so the degradation phase was inhibited using the autophagic tool drug CQ in combination to observe whether the expression level of LC3II was changed [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy can be both activated and inhibited in renal carcinoma, and it plays a double-edged role in the development of renal carcinoma [ 8 , 9 ]; in the early stage of cancer, autophagy can suppress tumors, while in the late stage, autophagy contributes to the survival of tumor cells in an unfavorable environment, and some autophagy-related proteins P62, LC3B, and beclin-1 have become indicators of the prognosis of patients with renal carcinoma [ 10 , 11 ]. Autophagy is a dynamically changing process [ 12 , 13 ], and this experiment was conducted to map the autophagy time point, and the results showed that the activation of autophagy was more obvious when ursolic acid acted on 786-O cells at 24 h. Therefore, the time point of the subsequent experiment was set to 24 h. It was found that ursolic acid could increase the expression level of LC3II protein in 786-O cells, which is considered as autophagy. However, the reason for this may be the increased autophagosome production and also the blocked degradation phase of autophagosomes, so the degradation phase was inhibited using the autophagic tool drug CQ in combination to observe whether the expression level of LC3II was changed [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Upon infection with the M41 variant, the viability and phagocytic function of macrophages are inhibited. Conversely, overall innate immunity was enhanced such as antimicrobial activity, toll like receptor (TLR) activation, and type I IFN or pro-in ammatory cytokine induction [35]. We detected a minimal number of activated macrophages that expressed MHCII molecules on their surface, probably because of the optimal inducing condition for myeloid cells was not provided.…”
Section: Discussionmentioning
confidence: 82%
“…Several genes including IFN-α, IL-1β, IL-6, etc. were significantly increased in these IBV-infected macrophages, and apoptosis was triggered by virus replication [ 28 ]. Overall, these results suggest macrophages play an important role in host innate and acquired immunity to resist IBV infection.…”
Section: Cells Involved In Innate Immunity After Ibv Infectionmentioning
confidence: 99%
“…It can also facilitate virus spread at a later stage of infection [ 81 ]. There have been reports about IBV-induced apoptosis both in vivo [ 55 ] and in vitro [ 28 , 82 ].…”
Section: Apoptosis Triggered By Ibv Infectionmentioning
confidence: 99%
See 1 more Smart Citation